Developing communicative LMS-based English for specific purposes learning materials with CLIL approach - Virginiya, Putu Tika; Natalia, Sang Ayu Made Krisna Dewi; Anggraheni, Raden Roro Rieta (LITERA, 2023)
Teaching English for Specific Purposes in the age of technological innovation necessitates a new strategy for communicative contexts that incorporates technology into the teaching and learning process. CLIL (Content and Language Integrated Learning) approach is considered a suitable approach in which students not only understand the content and context of situations that are practiced following the actual conditions in the industry but are also expected to be fluent in two-way communication. This study aims to develop an LMS-based communicative teaching material with the CLIL approach. Using the Research and Development method by applying the ADDIE model, 60 students were involved as the research subject, two lecturers were observed and interviewed, and three expert judges evaluated the quality of the communicative LMS-based materials developed. The results show that the developed materials were of excellent quality, with a mean score of 4.98 from the three expert judges, and the students have perfect perceptions towards both the LMS's features in English learning materials and the use of the CLIL approach in English learning materials. Pedagogically, it is advised that if internet access is unavailable, the lecturers figure out a means to get over last-minute obstacles.